Pulmonary melanocytic nevus – A case report with a mutation analysis of common driver oncogenes. Issue 11 (25th September 2019) - Tanaka, Meiro; Matsumura, Mai; Okudela, Koji; Mitsui, Hideaki; Tateishi, Yoko; Umeda, Shigeaki; Suzuki, Takehisa; Koike, Chihiro; Kataoka, Toshiaki; Kawano, Naomi; Kojima, Yui; Osawa, Hiroyuki; et al.
Abstract : Nevi are benign melanocytic tumors, and some nevi are considered to develop into malignant melanomas. Most nevi arise in the skin, but nevi occasionally occur in the conjunctiva, esophageal mucosa, or at other sites. Pulmonary melanocytic nevi are extremely rare, and only one case has been reported in the literature. Here, we present a case of pulmonary melanocytic nevus, involving a BRAF gene mutation (V600E), and we discuss the potential significance of this condition as a precursor to pulmonary malignant melanoma.